Pipelines 2019. proceedings of sessions of the Pipelines 2019 Conference, July 21-24, 2019, Nashville, Tennessee - Heidrick, Jeffrey W.; Mihm, Mark S. (American Society of Civil Engineers, 2019)
This collection contains 60 peer-reviewed papers on multidisciplinary topics, utility engineering, and surveying of utilities. Topics include: modeling and monitoring; pigging; multidisciplinary approaches to pipeline issues; pipe joints; pipe materials; and rehabilitation materials. This collection will be of interest to utility and pipeline owners, design and consulting engineers, contractors, manufacturers, suppliers, researchers, and pipeline professionals.
Keywords: Pipelines -- Maintenance and repair -- Congresses.; Water-pipes -- Evaluation -- Congresses.; Pipelines -- Design and construction -- Congresses.; Pipelines -- Inspection -- Congresses.; Sustainable construction -- Congresses.; elektronické knihy; electronic books